2008
DOI: 10.1089/scd.2008.0117
|View full text |Cite
|
Sign up to set email alerts
|

Defining Stem and Progenitor Cells within Adipose Tissue

Abstract: Adipose tissue-derived stem cells (ADSC) are routinely isolated from the stromal vascular fraction (SVF) of homogenized adipose tissue. Freshly isolated ADSC display surface markers that differ from those of cultured ADSC, but both cell preparations are capable of multipotential differentiation. Recent studies have inferred that these progenitors may reside in a perivascular location where they appeared to co-express CD34 and smooth muscle actin (α–SMA) but not CD31. However, these studies provided only limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
311
0
9

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 366 publications
(347 citation statements)
references
References 47 publications
27
311
0
9
Order By: Relevance
“…Some investigations have shown that hADMSCs recovered from the SVF are likely to be considered "pericytes" or "perivascular progenitor cells" (Caplan et al, 2008;Crisan et al, 2008;Lin et al, 2008). However, it is still unclear whether or not isolated hADMSCs are truly "pericytes" and from where hADMSCs originate (Locke et al, 2011;Tholpady et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have shown that hADMSCs recovered from the SVF are likely to be considered "pericytes" or "perivascular progenitor cells" (Caplan et al, 2008;Crisan et al, 2008;Lin et al, 2008). However, it is still unclear whether or not isolated hADMSCs are truly "pericytes" and from where hADMSCs originate (Locke et al, 2011;Tholpady et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we asked all authors to revisit the table and upgrade their part either by own data or based on additional literature, as necessary. This resulted in the upgraded Table 1 showing phenotypes of very small embryonic-like stem cells (vSELs) (5,6), neural stem cells (NSCs) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), hematopoietic stem cells (HSCs) from two organs (4,17), MSCs (4,18), EpSC (4), limbal epithelial stem cells (LSCs) (19), endothelial progenitor cells (EPCs) from different organs (3,4,(20)(21)(22)(23)(24)(25), supra-adventitial adipose stromal cells (SA-ASCs) (3,(22)(23)(24)(25), adipose pericytes (pericyte) (3,(22)(23)(24)(25), and finally cancer stem cells (CSCs) (26).…”
mentioning
confidence: 99%
“…VI (4) VII (19) VIII (20,21) IX (3,(22)(23)(24)(25) X (4) XI (3,(22)(23)(24)(25) XII (3,(22)(23)(24)(25) XIII ( (17) IV (4) V (4,18) VI (4) VII (19) VIII (20,21) IX (3,(22)(23)(24)(25) X (4) XI (3,(22)(23)(24)(25) XII (3,(22)(23)(24)(25) XIII (26) RHAMM/HMMR marker expression in the same stem cell lineage obtained from various tissues may indicate differences in their pluripotency. It is also possible that stem cell marker expression pattern and levels depend on respective cell cycle phases.…”
mentioning
confidence: 99%
“…35,36 Recently, MSCs derived from the stromal vascular fraction of adipose tissue, termed as adipose tissue-derived stem cells (ADSCs), represent an abundant and easily accessible source of stem cells. 37 While bone marrow is obtainable in the gram range by a painful marrow aspiration procedure, adipose tissue can be obtained in the range of hundreds of grams with a minimally invasive procedure. The possibility of harvesting hundreds of grams of adipose tissue excludes the need for MSC isolation and culture steps and allows for the direct re-injection of the stromal vascular fraction during the same surgical procedure in which they were harvested.…”
Section: Stem Cells and Sourcesmentioning
confidence: 99%
“…Therefore, it is reasonable to expect that ADSCs will become the preferred choice of ASCs for future clinical applications. 37 Localisation of ASCs in their native tissue-stem cell niche The stem cell niche is a microenvironment that maintains stem cells in a quiescent state. After tissue injury, the niche promotes either selfrenewal or differentiation to form new tissues.…”
Section: Stem Cells and Sourcesmentioning
confidence: 99%